2008
DOI: 10.1097/hjh.0b013e3282f2fdb6
|View full text |Cite
|
Sign up to set email alerts
|

Association of augmentation index of radial pressure wave form with diurnal variation pattern of blood pressure in untreated patients with essential hypertension

Abstract: The present study revealed that augmentation index was associated with dipping blood pressure patterns in untreated hypertensive patients aged 60 years or younger. Augmentation index determination would be useful for initial assessment in connection with possible abnormal diurnal blood pressure variability in patients with age 60 years or younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
1
15
1
1
Order By: Relevance
“…The first study to address this issue, 23 which evaluated 106 untreated hypertensive individuals, found that aortic PWV was an independent predictor of the nocturnal SBP reduction. Similarly, three other studies [24][25][26] reported significant associations between the non-dipping pattern and arterial stiffness. Abbreviations: HDL, high-density lipoprotein; SBP, systolic blood pressure; PP, partial pressure; UAER, urinary albumin excretion rate.…”
Section: Discussionmentioning
confidence: 99%
“…The first study to address this issue, 23 which evaluated 106 untreated hypertensive individuals, found that aortic PWV was an independent predictor of the nocturnal SBP reduction. Similarly, three other studies [24][25][26] reported significant associations between the non-dipping pattern and arterial stiffness. Abbreviations: HDL, high-density lipoprotein; SBP, systolic blood pressure; PP, partial pressure; UAER, urinary albumin excretion rate.…”
Section: Discussionmentioning
confidence: 99%
“…8 AI can be determined noninvasively by pulse wave analysis of the radial artery, and provides information on cardiac load and vascular properties. 9,10 The usefulness of AI measured from radial pressure waveform has been shown in earlier studies. 10,11 As another parameter of arterial stiffness, the cardio-ankle vascular index (CAVI), which reflects the stiffness of the aorta independently of blood pressure, has been developed recently.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The usefulness of AI measured from radial pressure waveform has been shown in earlier studies. 10,11 As another parameter of arterial stiffness, the cardio-ankle vascular index (CAVI), which reflects the stiffness of the aorta independently of blood pressure, has been developed recently. 12 CAVI was reported to be associated with atherosclerosis, 13 cardiovascular risk factors 14 and LV diastolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ND attenuation was associated with the presence of other cardiovascular risk factors (obesity and lower HDL-c) and also with a higher frequency of lesion in target-organ. Studies on the prevalence of cardiovascular and cerebral events varies greatly in the specific literature (Table 5), reaching a frequency of 37.5 to 64.2% [11][12][13][14][15][16][17][18][19][20][21] under several factors' influence, like the definition of sleep and vigil periods 22 .…”
Section: Discussionmentioning
confidence: 99%